Fatores de risco individuais e familiares no desenvolvimento da pré-eclâmpia - Pereira, Flavio Venício Marinho (2010)
Preeclampsia is a spectral disease, with different clinical forms which can evolve with severe multisystemic complications. This present study aimed to determine the risk factors associated with preeclampsia (PE); to validate the existence of aggregation of hypertensive disease in families of women with preeclampsia and verify the existence of association between polymorphisms in the VEGF gene and level of VEGF and its soluble receptor (sFlt1). A case-control study was performed (n = 851). Genotyping of VEGF was performed and serum levels of VEGF and sFlt1 were measured by ELISA. It was observed that 38% of mothers (173, 455) of a case of preeclampsia and 30.8% (78 of 361) of controls had history of hypertension (p <0.0001). Similarly, when examining the history of maternal preeclampsia, we observed that 14.6% (48 of 328) of mothers of women with preeclampsia and 9.6% (12 of 294) of mothers of controls had a history of preeclampsia (p = 0.0001). As for maternal history of preeclampsia, we found that 5.1% (15 of 295) of cases and 3.6% (7 of 314) of controls had a history of preeclampsia (p = 0.0568). Sisters of women with preeclampsia also had a history of hypertensive disease in 9% (41 of 455) versus 6.6% (13 of 361), p = 0.002. Similarly when examining the history of preeclampsia in sisters, it was observed that 22.7% (57 of 251) of a sister of case versus 11.4% (26 of 228) of controls had a history of preeclampsia (P = 0.0011). We observed a decrease in free VEGF in the serum of patients (P <0.05) and increased soluble VEGF receptor. There was no association between polymorphisms in the VEGF gene and preeclampsia. The data obtained in this work validate that hypertensive disease in mothers and sisters with preeclampsia are risk factors for preeclampsia. The risk of illness in the family is higher according to disease severity. High incidence of preeclampsia can be assumed by the high incidence of this disease among the controls. Significant differences between the frequency of preeclampsia in mothers of cases and controls indicate familial factors. Work is being conducted with the to eventually perform genome wide association studies to identify susceptibility loci